(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
While etymological nasals in inherited /VN.T/ sequences are normally noted in Hispano-Celtic homoörganically to the heterosyllabic plosive, two other orthographic practices are attested in the corpus: (a) the nasal is not noted at all; (b) the nasal is noted heteroörganically to the plosive. These practices have always been treated as discrete phe- nomena. In this paper, all three practices are united as symptoms of a single phonological process whose varying outcomes are the product of differences in the timing of the gesture which articulates the place of the nasal.